Analysis of factors influencing the use of new forms of foreign language textbooks from the perspective of sociocultural theory - He, Jingjing; Lv, Hui (Frontiers in Education, 2025)
Few attempts have been made to explore the use of new-form foreign language textbooks. Adopting an empirical research method from the perspective of sociocultural theory, this research generalizes and describes five dimensions in the use of new-form foreign language textbooks and nine factors contained therein, and constructs structural equation model to summarize the relationships and interactive effects among the dimensions. Results of statistical analyses show that textbook design, teacher factors, student factors, teaching resources and teaching environment constitute the use of new-form foreign language textbooks, among which digital tools and technological support have direct effect on textbook design and teaching environment. Moreover, cross-cultural competence and digital literacy produce a significant effect on teacher and student factors. Results also indicate that authentic language materials and collaborative learning have a direct and significant effect on teaching resources. In short, this research integrates AI tools and learner-centered goal in the use of new-form foreign language textbooks, promoting students’ cross-cultural communication in a highly interactive learning environment.